Systematic review of training environments with motor imagery brain-computer interface: coherent taxonomy, open issues and recommendation pathway solution - Albahri, A. S. (Tanjung Malim, 2021)
Systematic review of training environments with motor imagery brain-computer interface: coherent taxonomy, open issues and recommendation pathway solution by Albahri, A. S.